TRADISI SUKU ASMAT DALAM ROMAN NAMAKU TEWERAUT KARYA ANI SEKARNINGSIH - Insum Malawat; Hengki Mofu (Universitas Negeri Makassar, 2018)
This research aims at describing Asmat tradition in romance Namaku Teweraut (NT) written by Ani Sekarningsih. The study was designed with a literary anthropological approach. Data comes from Roman NT. Data collection is done through a note-taking method. Based on the result of the analysis, it is concluded that romance NT contains following traditions: matchmaking, dowry payment, and giving birth. These traditions tend to be gender bias. It can be seen from wife position in a family. A wife is always in weak, margin, and threat position. Romance NT contains patriarchal conservatism culture that becomes the root of practical life of gender bias stereotype to the women in Asmat society.